Reframing Jewish Forms of Speaking to God: The Use of Apostrophe in David Rosenmann-Taub’s Cortejo y epinicio - Raelene C Wyse (Studies in 20th & 21st Century Literature, 2018)
In his first published collection of poetry, Cortejo y epinicio (‘Cortege and Epinicion,’ 1949), Chilean author David Rosenmann-Taub (1927) depicts speakers experiencing crises of faith. They question what God is and what it means to believe, as they seek out pagan, earthly, Christian, and Jewish forms of relating to the divine. My analysis foregrounds the distinct presence of Jewishness in Cortejo y epinicio to analyze how Rosenmann-Taub represents cross-cultural spaces, heterogeneity, and heterodoxy as part of Chilean poetry and culture. One of the central means in which Rosenmann-Taub explores Jewish forms of relating to God is through the use of apostrophe. First, I offer a theoretical framework for discussing apostrophe in poetry and prayer. Then, I use this framework to analyze three poems–“Elegía y Kadisch” ('Elegy and Kaddish'), “Gólgota” ('Golgotha') and “Schabat” ('Shabbat')–that depict speakers talking to or about God. Considering the poems alongside the prayers and conventions to which they refer, I read the poems as rewritten prayers to God. This comparison not only highlights the notable presence of cross-cultural forms in Rosenmann-Taub’s poetry, but also points to how he challenges and reframes them. The poem’s speakers work toward collapsing the boundaries between belief and disbelief, earthly and divine, secular and religious, as they construct faith as a dynamic, earthly, and heterodoxical mode of being.
Keywords: David Rosenmann-Taub; Cortejo y epinicio; Twentieth Century Latin American Poetry; Chilean Poetry; Twentieth Century Latin American Literature